Isoperistaltic gastric tube for long gap esophageal atresia (LGEA) in newborn, infants, and toddlers: a case-control study from a tertiary center - Zarfati, Angelo; Tambucci, Renato; Bagolan, Pietro; Conforti, Andrea (Frontiers in Pediatrics, 2023)
BACKGROUND: limited evidence exists about outcomes after gastric tube formation as a last chance technique to avoid esophageal replacement in long gap esophageal atresia (LGEA). The last ERNICA Consensus Conference on the Management of LGEA has defined this among the priorities for future research. AIMS: analyze our experience with Isoperistaltic Gastric Tube (IGT) and compare its outcomes with other techniques. METHODS: a case-control study has been conducted. A retrospective monocentric analysis of LGEA patients (period: 2010-19) has been undertaken. Five IGT patients have been identified and each of these has been type matched with two cases of LGEA treated with other techniques. The follow-up (FU) considered was 24-months. RESULTS: IGT and controls showed no statistically significant differences regarding preoperative variables like sex, gestational age, birth weight, syndromes, and EA type. However, IGT patients had a significantly longer esophageal GAP (4.5 vertebral bodies vs 3.6, p=0.019) at time of surgery. The analysis showed no statistical difference among the two groups about operative outcomes, ICU or overall postoperative stay. No differences emerged between IGT and controls during the follow-up for GERD, esophagitis, fundoplication, dysphagia, vocal cord paralysis, stenosis and dilatations, auxologic data, need for revision, oral aversion, and death. CONCLUSIONS: Isoperistaltic Gastric Tube was safe and effective even in LGEA patients with longer gaps, with good perioperative, post-operative and middle-term outcomes. This procedure may be considered as a possible alternative to avoid an esophageal substitution when a primary anastomosis seems impossible for a residual gap.